Faktor-Faktor Profitabilitas yang Mempengaruhi Tax Avoidance - Ismail Slamet Prehatina; Rifkhan (Syntax Corporation Indonesia, 2024)
This study aims to determine the profitability factors of tax avoidance. The research method used in this study used secondary data taken from the official website of the Indonesia Stock Exchange and the website of each company. The population in this study is consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2016-2022. The sampling method in this study is purposive sampling. Companies that meet the criteria are 13 companies from a total population of 118 companies, so that the total number of samples in this study is 91 company data that meet the criteria. The variables used in this study are gross profit margin (X1), net profit margin (X2), return on investment (X3), return on equity (X4) and earning per share (X5) as independent variables and tax avoidance (Y) as the dependent variable. The data analysis technique used is regression analysis of panel data using statistical eviews software. The results of this study state that: Net profit margin affects tax avoidance. Gross profit margin, return on investment, return on equity and earnings per share have no effect on tax avoidance. Gross profit margin, net profit margin, return on investment, return on equity and earning per share simultaneously affect tax avoidance.